Analisis Pemasaran Dan Kelayakan Bisnis Jamur Tiram Di Kabupaten Bogor (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
Horticulture can be interpreted as one of the agricultural subsectors that bridges the gap between production and consumption in Indonesian society. Horticultural commodities consist of vegetables, fruit, ornamental plants and medicinal plants. One of the horticultural commodities is mushrooms. Mushroom commodities have quite high consumption value in Indonesia. The demand for mushrooms continues to increase, but the availability of inputs is still inadequate and farmers still rely on marketing institutions, which is still an obstacle for mushroom entrepreneurs to meet consumer demand. Based on these problems, it is necessary to add mushroom cages so that the level of mushroom productivity continues to increase and an efficient marketing channel is needed so that all actors involved in the marketing channel can benefit each other. Research uses qualitative and quantitative methods. The data sources used are primary and secondary data. The analysis results from the business feasibility study can be run properly and inefficient marketing channels are found in channel 3.